Upaya Meninjau Pilihan Rest Area yang Optimal: Dampak Lokasi, Ragam Fasilitas, dan Lingkungan Alam - Rahayu Mardikaningsih; Ana Arifiana; Siti Nur Haliza; Didit Darmawan; Utami Puji Lestari (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Planning for extended journeys often demands meticulous preparation, which encompasses the careful selection of suitable rest stops en route. This research endeavors to ascertain the influence of location, range of amenities, and the surrounding environment on the decision-making process regarding rest area preferences among operators of the Surabaya Mojokerto toll road. Employing a quantitative methodology, this investigation engaged in the collection of data through a web-based survey involving 120 chosen respondents who are frequent long-distance travelers. The research methodology utilized purposive sampling. The outcomes of the data analysis divulge the pivotal role of location in shaping rest area selections. Elements such as accessibility from primary thoroughfares and the proximity of notable landmarks to these rest areas wield a discernible impact on preference formation. Additionally, the diversity of services proffered within these rest areas significantly influences traveler choices. The availability of dining establishments, relaxation zones, and retail outlets within the rest areas substantially contributes to the overall quality of the restful sojourn. Moreover, the natural environs encircling these rest areas emerge as a noteworthy determinant. The innate charm of the natural landscape and the availability of verdant open spaces bestow an added positive dimension upon the rest areas. Respondents demonstrated a marked inclination toward opting for rest stops that afford captivating natural vistas and an organic ambiance